Online Learning and Scientific Literacy in Elementary Schools during the Covid-19 Pandemic - Salma Ihsani Fhilrizki; Wahyu Sopandi; Irfan Fauzi (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThis study aims to investigate the relationship between online learning and scientific literacy of students in fifth grade of elementary school in the Covid-19 era. Employing a correlational research design, this study involved 54 fifth grade students of an elementary school in Bandung City, Indonesia. The data were collected using a scientific literacy test referring to the indicators of PISA 2018 and a questionnaire in an online learning evaluation. The analysis of the data was carried out using descriptive statistics through calculating the average and percentage scores. The data were also analyzed using inferential statistics in the form of the Pearson correlation test to determine the relationship between online learning and scientific literacy. The results of this study revealed that, based on the Pearson correlation test, the sig score was 0.81. There was no relationship between online learning and scientific literacy of fifthgrade students of elementary school. Therefore, efforts should be made to improve the scientific literacy of elementary school students, one of which is through optimizing online learning.Keywords: online learning, scientific literacy, elementary school.Â Â AbstrakPenelitian ini bertujuan untuk menyelidiki hubungan antara pembelajaran daring dengan literasi sains siswa kelas 5 sekolah dasar (SD) di era Covid-19. Dengan menggunakan desain penelitian korelasi, penelitian ini melibatkan 54 siswa kelas 5 sekolah dasar di Kota Bandung, Indonesia. Data diperoleh dengan menggunakan tes literasi sains yang merujuk pada indikator PISA 2018 dan kuesioner pada evaluasi pembelajaran daring. Analisis data dilakukan dengan menggunakan statistik deskriptif dengan menghitung skor rata-rata dan persentase. Data juga dianalisis menggunakan statistik inferensial berupa uji korelasi Pearson untuk mengetahui hubungan antara pembelajaran online dan literasi sains. Hasil penelitian ini menunjukkan bahwa, berdasarkan uji korelasi Pearson, diperoleh skor sig 0,8. Pembelajaran online tidak memiliki hubungan dengan literasi sains siswa kelas 5 sekolah dasar. Maka dari itu, perlu ada upaya untuk meningkatkan literasi sains siswa sekolah dasar, salah satunya dengan mengoptimalkan pembelajaran online.Kata kunci: pembelajaran online, literasi sains, sekolah dasar.